Surface Analytical Investigation on Organometal Triiodide Perovskite. Issue 1735 (31st May 2016) - Li, Youzhen; Xu, Xuemei; Wang, Chenggong; Wang, Congong; Xie, Fangyan; Huang, Jinsong; Gao, Yongli
ABSTRACT: Lead halide perovskites have proven their great power conversion efficiency (PCE) in the last few years and attracted more and more attentions. Evaporation is an important method to get high quality perovskite films, especially for surface and interface investigation, which is important for the solar cell performance. In this paper, we present our investigations on growing PbI2 and CH3 NH3 I films by evaporation, and then CH3 NH3 PbI3 films by co-evaporation. X-ray photoemisson spectroscopy (XPS) was used to characterize the films. The results showed that CH3 NH3 I film was not stable in vacuum. Both N and I decreased in vacuum with time elapsing. PbI2 and CH3 NH3 PbI3 films are quite stable. The atomic ratio of CH3 NH3 PbI3 films (C: N: Pb: I =1.29:1.07:1.00:2.94) is very close to the ideal CH3 NH3 PbI3, which indicates that evaporation is a good method to get high quality perovskite films with accurate atomic ratio.